If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 25 = 30 Reorder the terms: 25 + 2x = 30 Solving 25 + 2x = 30 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25' to each side of the equation. 25 + -25 + 2x = 30 + -25 Combine like terms: 25 + -25 = 0 0 + 2x = 30 + -25 2x = 30 + -25 Combine like terms: 30 + -25 = 5 2x = 5 Divide each side by '2'. x = 2.5 Simplifying x = 2.5
| 8x^2+18x-11=0 | | 4x-2(1+3x)=5-3(x+2) | | 0.6x-1.5=1.8 | | 9x+3x-10=6x+3x | | Y-7=4 | | 2x-3(x+4)=-5 | | -10=-8+7 | | 19x^7-12x^5+5x^4= | | -3(5-6)-4(2-3)= | | 3=3x-1 | | 12x+36=24+12x | | 0=2x^3-3x^2+13x-6 | | 17+2.6b=30 | | 6=2x^2-3x+13 | | 18x=216 | | M+4=9 | | 10x-21=7x | | 441t^2x(3s-5k)=5s+3k^2 | | Z-5=7-1(3+z) | | 14x+1=13+12x | | 3x+6=x | | -10z-6-3z=8+z | | 12a-4=44 | | 2(1-2y)=4y+18 | | m+3m=4+2m | | 5x-12=3x | | 7x+30=12x | | 5x=x+20 | | 123(45)=kl | | 10x=y | | p-3q=-1 | | j(s)=j+3 |